The role of non-coding RNA regulates stem cell programmed death in disease therapy - Ziling Liao; Weidong Liu; Lei Wang; Wen Xie; Chaoyan Yao; Qianping Huang; Xingjun Jiang; Caiping Ren (Non-coding RNA Research)
Programmed cell death (PCD), an essential and inevitable phenomenon, is integral to organismal development. It not only maintains cellular homeostasis but also prevents aberrant cell proliferation, thereby protecting normal growth and development from detrimental factors. And it is governed by a highly complex and sophisticated regulatory network in which non-coding RNAs (ncRNAs) play pivotal roles. ncRNAs refer to RNA molecules that do not encode proteins and encompass various types, including long non-coding RNA (lncRNA), microRNA (miRNA), and circular RNA (circRNA). Herein, we investigate the specific signaling mechanisms by which ncRNAs regulate stem cells, elucidating their role in modulating PCD process through interactions with specific molecules. We further summarize the impact of above modulating role on stem cell differentiation, proliferation, cycle regulation and diverse disease development and therapy. Additionally, given the emerging trends in the therapeutic application of ncRNAs and stem cells, we explore the potential of their combined application for disease treatment.